Planning the size of variety field trials with forest trees - Krusche, D.=700 1 Padro, A.
(En, Es)
Ilus., ref
Keywords: ARBOLES FORESTALES; ENSAYOS DE VARIEDADES; MUESTREO; ESPAÑA; ANALES DEL I.N.I.A.